Bioactive specialised metabolites from the endophytic fungus Xylaria sp. of Cudrania tricuspidata. (April 2022) - Song, Jintong; Xu, Ke; Liu, Chunyu; Wang, Tian; Luan, Xiaoyi; Zhu, Lihua; Chu, Zhaojun; Fu, Xiaojie; Chang, Wenqiang; Wang, Xiaoning; Lou, Hongxiang
Abstract: Fourteen undescribed compounds, including five 2, 5-diarylcyclopentenones xylariaones A1−B2, seven α -pyrone derivatives xylaripyones A−G, one γ -pyrone derivative xylaripyone H, one diketopiperazine cyclo-( L -Leu- N -ethyl- L -Glu), and two known diketopiperazines, were isolated from cultures of the endophytic fungus Xylaria sp., which was separated from Cudrania tricuspidata Bureau ex Lavallée. Their structures were determined by analysing extensive spectroscopic data (HRESIMS and NMR) and electronic circular dichroism (ECD) calculations. Furthermore, these compounds were evaluated for potential antiproliferative activity against the human tumour cell lines PC3 and A549, and the results showed that xylaripyone D exhibited moderate inhibitory activity against the proliferation of PC3 cell lines with an IC50 value of 14.75 μ M. Meanwhile, xylariaone A3 and xylaripyone F displayed weak inhibitory effects on NO production in RAW 264.7 murine macrophages with IC50 values of 49.76 and 69.68 μ M, respectively. Graphical abstract: Image 1 Highlights: Fourteen undescribed compounds were isolated from the endophytic fungus Xylaria sp. Xylaripyone D exhibited moderate inhibitory activity against the proliferation of PC3 cell lines. Xylariaone A3 and xylaripyone F displayed weak inhibitory effects on NO production in RAW 264.7 murine macrophages.